Social work practice and men who have sex with men - Joseph Sherry (New Delhi Sage, 2005)
The book argues that understanding the stress that men who have sex with men experience and their coping strategies will assist sympathetic groups and professionals to work with this community.
Keywords: Gay men; Homophobia; Homosexuality; India; Social work with gays